1987
DOI: 10.2486/indhealth.25.19
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of acrylamide in developing rat brain: Changes in the levels of brain biogenic amines and activities of monoamine oxidase and acetylcholine esterase.

Abstract: : Levels of biogenic amines and activities of monoamine oxidase and acetylcholine esterase were investigated in developing rat brain following acrylamide (ACR) exposure. The ACR exposed rats showed a significant reduction in noradrenaline (NA), dopamine (DA) and 5-hydroxytryptamine (5-HT) contents at 4, 8 and 15 days of age whereas the adult animals exhibited no such changes.Exposure of rats to ACR resulted in decrease of NA levels in basal ganglia, pons medulla and mid brain regions and of DA in cerebellum, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
2
11
1
Order By: Relevance
“…Acrylamide at a high dose is known to increase the activity of monoamine oxidase and decrease that of acetylcholinesterase in the developing rats and increase the striatal dopamine receptors in adult rats (Agrawal et al, 1981a(Agrawal et al, , 1981bHusain et al, 1987). Opposite effects as reflected by a decrease in the activity of monoamine oxidase and striatal dopamine receptors in our study may probably be due to nutritional influ-LPD LPD+ACR…”
Section: Discussioncontrasting
confidence: 57%
“…Acrylamide at a high dose is known to increase the activity of monoamine oxidase and decrease that of acetylcholinesterase in the developing rats and increase the striatal dopamine receptors in adult rats (Agrawal et al, 1981a(Agrawal et al, , 1981bHusain et al, 1987). Opposite effects as reflected by a decrease in the activity of monoamine oxidase and striatal dopamine receptors in our study may probably be due to nutritional influ-LPD LPD+ACR…”
Section: Discussioncontrasting
confidence: 57%
“…Exposure to the monomer has also been found to alter the neurotransmitter levels, their receptors and associated enzymes involved in the metabolism of neurotransmitters and cause neurotoxicity (Agarwal et al, 1981;Ali et al, 1983;Husain et al, 1987). Enhanced striatal dopamine receptors and decreased GST activity were reported to be the primary changes in acrylamide neurotoxicity in rats since no toxic effect on these parameters was observed following treatment with N,N'-bis acrylamide, a non-neurotoxic analogue .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reviewed by SCF (2002), JECFA (FAO/WHO, 2011) and ATSDR (2012). Husain et al (1987) reported significantly decreased levels of selected catecholamines (noradrenaline, dopamine, 5-hydroxytryptamine) in brains of pups of Wistar albino rat dams administered AA at 25 mg/kg per day during lactation. Levels of brain catecholamines were affected in a similar way in rat pups at 12-21 days of age at the beginning of a 5-day period in which they were administered AA by gavage at 25 mg/kg per day, whereas these effects were not seen in rat pups that were 60 days of age at the initiation of dosing.…”
Section: Developmental Toxicitymentioning
confidence: 97%